Adaptive settlements toward flooding in the riverbanks of Meureudu Rriver Indonesia / Mirza Irwansyah, Cut Nursaniah and Laila Qadri - Irwansyah, Mirza; Nursaniah, Cut; Qadri, Laila (2018)
Meureudu Riverbanks, was a pioneer place of a collective settlements, that was developed than eventually became a City of Meureudu in Aceh Province, Indonesia. Initially it formed as traditional fishermen settlements but has now shifted into modern settlements. However, the settlements have developed sporadically to form an unplanned pattern of settlements. This condition has resulted in low maintaining river, and has not adapted to the existence of the dwelling with the environment. Floods occur repeatedly in the river that affects the community. This study aimed to find the residential pattern design and adaptive settlements with Meureudu River watersheds. Easy and close access roads to markets created economy of the people in motion. This has also caused large number of unbridled migrants to enter and build the settlements. The method used is a combination of quantitative methods based on interview data and questionnaires and qualitative exploratory methods based on field observation. The data were collected through observation, field measurement and secondary data sources. The results show that the condition of settlements along the river basin do not reflect the culture of the river. In order not to further aggravate the condition of the settlement and its impact on the occupants, two types of houses, namely in the form of stage and non-stage are recommended. The stage house is located on the riverfront with an orientation overlooking the river. Undersea area can be used as security from the puddle of river water runoff during the flood and as a garden area and public while dry, while at a distance of 100 meters from the river non-stage house form might be built because the runoff of flood water can no longer affect on occupancy.